Protocol Relating to the Madrid Agreement Concerning the International Registration of Marks adopted at Madrid on June 27, 1989, as amended on October 3, 2006, and on November 12, 2007 : Regulations under the Protocol Relating to the Madrid Agreement Concerning the International Registration of Marks (as in force on February 1, 2021), Administrative instructions for the application of the Protocol Relating to the Madrid Agreement Concerning the International Registration of Marks (as in force on February 1, 2021), Schedule of fees, (as in force on February 1, 2020) - World Intellectual Property Organization (Geneva, Switzerland WIPO, 2021)
La presente publicación contiene los textos del Protocolo relativo al Arreglo de Madrid relativo al Registro Internacional de Marcas (en adelante, el "Protocolo") (1989), modificado en 2006 y en 2007, el Reglamento del Protocolo relativo a la Arreglo de Madrid relativo al Registro Internacional de Marcas, las Instrucciones Administrativas para la Aplicación del Protocolo y el Arancel de Tasas." -- Prefacio.
Keywords: MARCAS DE FABRICA -- DERECHO INTERNACIONAL; MADRID - PROTOCOLO